Analisis Perkembangan Desa Yang Sedang Berkembang - Dian G Purba; Manres M.Nababan; Monika Siallagan; Yosi Irawelda W. Saragih; Rizky Sahertian; Muhammad Fauzi; Roni Agung Hasibuan; Rafael Siregar; Ahmad Tarez; Stepan Purba; Jun Kifran Manik (Lembaga Pengembangan Kinerja Dosen, 2024)
The study aims to determine the development of the village Talun Kondot seen: livelihoods, production, education, institutions, infrastructure, technology, customs and levels of development Talun kondot village. The research was conducted in the village of Talun Kondot Panombeian Subdistrict Data collection technique used documentation study. The analysis technique used is descriptive qualitative analysis techniques. Research shows that: (1 The livelihood of the people in Talun Kondot is in the agricultural sector, namely growing rice, palm oil, rubber, corn and snake fruit.(2) average income is around 2 million to 2 million 500, (3) education level 60% have graduated from elementary school and some have even graduated from college, (4) existing institutions consist of government institutions, social institutions, educational institutions, economic institutions , health institutions, and the 5 institutions are running well, (5) infrastructure already provided more than 4, namely infrastructure and transport infrastructure, education facilities, health facilities, electric utilities, communications and clean water supply, (6) the application of agricultural technology has been implemented.